What is the potential of neurostimulation in the treatment of motor symptoms in schizophrenia?. (2nd July 2020) - Lefebvre, Stephanie; Pavlidou, Anastasia; Walther, Sebastian
ABSTRACT: Introduction: Motor abnormalities in schizophrenia are frequent and linked to poor social functioning and low quality of life. To date, there are no effective treatments available to alleviate these motor impairments. Previous studies have linked altered connections within the cerebral motor circuits to motor abnormalities. Areas covered: This perspective article will discuss the efficacy of noninvasive brain stimulation (NIBS) techniques as a potential therapeutic tool in improving motor impairments in schizophrenia. Expert opinion: The cortical motor network is easily accessible using NIBS, which has been proven reliable in restoring motor functioning across different pathologies. It is important to establish protocols that explore optimal treatment targets, timing, and duration of the stimulation, as well as, the standardization of motor assessments in order to compare across different brain stimulation methodologies. The authors believe NIBS to be ideal in restoring and improving motor impairments in schizophrenia.